Ultrasound intima media thickness cut-off values for cranial and extracranial arteries in patients with suspected giant cell arteritis - López-Gloria, Katerine; Castrejón, Isabel; Nieto-González, Juan Carlos; Rodríguez-Merlos, Pablo; Serrano-Benavente, Belén; González, Carlos Manuel; Monteagudo Sáez, Indalecio; González, Teresa; Álvaro-Gracia, José María; Molina-Collada, Juan (Frontiers in Medicine, 2022)
Objective To determine the optimal ultrasound (US) cut-off values for cranial and extracranial arteries intima media thickness (IMT) to discriminate between patients with and without giant cell arteritis (GCA). Methods Retrospective observational study including patients referred to an US fast-track clinic. All patients underwent bilateral US examination of the cranial and extracranial arteries including the IMT measurement. Clinical confirmation of GCA after 6 months was considered the gold standard for diagnosis. A receiver operating characteristic (ROC) analysis was performed to select the cut-off values on the basis of the best tradeoff values between sensitivity and specificity. Results A total of 157 patients were included, 47 (29.9%) with clinical confirmation of GCA after 6 months. 41 (87.2%) of patients with GCA had positive US findings (61.7% had cranial and 44.7% extracranial involvement). The best threshold IMT values were 0.44 mm for the common temporal artery; 0.34 mm for the frontal branch; 0.36 mm for the parietal branch; 1.1 mm for the carotid artery and 1 mm for the subclavian and axillary arteries. The areas under the ROC curves were greater for axillary arteries 0.996 (95% CI 0.991–1), for parietal branch 0.991 (95% CI 0.980–1), for subclavian 0.990 (95% CI 0.979–1), for frontal branch 0.989 (95% CI 0.976–1), for common temporal artery 0.984 (95% CI 0.959–1) and for common carotid arteries 0.977 (95% CI 0.961–0.993). Conclusion IMT cut-off values have been identified for each artery. These proposed IMT cut-off values may help to improve the diagnostic accuracy of US in clinical practice.